Evaluasi Efektivitas Sistem Manajemen Mutu ISO 9001:2015 pada PT. Wellgan Gemilang - Massie, Febita Gioviansisca; Raharjo, Jani (Jurnal Titra, 2019)
This research was conducted to evaluate the ISO 9001: 2015 Quality Management System at PT. Wellgan Gemilang. The implementation of the ISO 9001:2015 Quality Management System (QMS) at PT. Wellgan begins with a decision (Gap Analysis) between the requirements of the ISO 9001: 2015 QMS and the fulfillment of the documents which PT. Wellgan has and the implementation of the company. The results of the initial gap analysis were 61.97%, still requiring fulfillment of ISO 9001:2015 requirements by making documents which are required by ISO 9001: 2015. QMS. The design and manufacturing of documents are document control, design and development, inappropriate product control, Audit Internal and management meetings. The socialization of the implementation of ISO 9001:2015 QMS has been carried out by Top Management and all staff of PT. Wellgan Gemilang. Evaluating the effectiveness of implementing ISO 9001: 2015 QMS has been done by conducting an internal audit. Internal audit results found 1 minor findings (the system did not run properly) and 12 observations (increases). The findings of 1 minor and 12 observations shows that PT. Wellgan were effective in implementing ISO 9001: 2015. The final gap analysis shows that the fulfillment of costs based on the ISO 9001: 2015 clause is 91.43%.